Room Monitoring System Using OpenWRT-Based Webcam - Arif Setiawan; Ahmad Subhan Yazid; M Didik Rohmad Wahyudi (IJID (International Journal on Informatics for Development), 2015)
The development of Closed Circuit Television (CCTV) technology makes it easier for a user to monitor a room. However, the use of CCTV still cannot reach all levels of society due to the price is relatively expensive. Therefore, it is necessary to build a new system that has the same features as CCTV devices in general but at a more affordable price. This system was built using the OpenWRT operating system. The operating system will be installed on a wireless router with several additional tools to support its functionality such as speakers, GSM modems, webcams, and flash drives. The resulting system has the ability to detect movement and store images and videos when suspicious movements are detected. In addition, this system also has several other features such as alarm alerts, Short Message Service (SMS) warnings, user email reports, and easy access via WIFI and the internet.